New Age Herbals Resource, Quality and Pharmacognosy (Springer Singapore, 2018)
Importance of herbs (medicinal plants) can hardly be overemphasized. They are exploited for manyfold applications, ranging from phytopharmaceuticals, to nutraceuticals, to cosmetics and many others. Keeping in view the richness of herbs and their vast potential, this book collates the most up-to-date knowledge of important herbs and herbals. The book also gives an overview of some issues causing hindrance in the promotion of herbals. This book attempts to compile the rich experience of experts working on various herbs. New age single plant species, having multiple medicinal traits worth exploiting i.e. Hippophae rhamnoides (seabuckthorn), and Morinda citrifolia (noni) also find place as full chapters in the book.